Using in vitro bioassays to guide the development of safer bio-based polymers for use in food packaging - Harper, Emma; Cunningham, Eoin; Connolly, Lisa (Frontiers in Toxicology, 2022)
Petroleum-based polymers traditionally used for plastic packaging production have been shown to leach dangerous chemicals such as bisphenol-A (BPA). Bio-based polymers are potentially safer alternatives, and many can be sustainably sourced from waste streams in the food industry. This study assesses bio-based polymers undergoing food packaging development for migration of endocrine disrupting leachates at the level of estrogen, androgen and progestagen nuclear receptor transcriptional activity. Reporter gene assays were coupled with migration testing, performed using standardised test conditions for storage and temperature. Test samples include nine bio-based polymers and four inorganic waste additives mixed with a traditional petroleum-based polymer, polypropylene. Thermoplastic starch material, polybutylene succinate, polycaprolactone, polybutylene adipate terephthalate (PBAT), two polylactic acid (PLA)/PBAT blends, polyhydroxybutyrate (PHB) and eggshell/polypropylene (10:90) presented no significant reduction in metabolic activity or hormonal activity under any test condition. Polypropylene (PP) presented no hormonal activity. Metabolic activity was reduced in the estrogen responsive cell line after 10 days migration testing of eggshell/polypropylene (0.1:99.9) in MeOH at 40°C, and PP in MeOH and dH20. Estrogenic agonist activity was observed after 10 days in poultry litter ash/polypropylene (10:90) in MeOH at 20 and 40°C, poultry feather based polymer in MeOH and dH2O at 40°C, and eggshell/polypropylene (40:60) and PLA in dH2O at 40°C. Activity was within a range of 0.26 - 0.50 ng 17β-estradiol equivalents per ml, equating to an estrogenic potency of 3 to ~2800 times less than the estrogenic leachate bisphenol-A. Poultry litter ash/polypropylene (10:90) in MeOH for 10 days presented estrogenic activity at 20 and 40°C within the above range and anti-androgenic activity at 40°C. Progestagenic activity was not observed for any of the compounds under any test condition. Interestingly, lower concentrations of eggshell or PP may eliminate eggshell estrogenicity and PP toxicity. Alternatively eggshell may bind and eliminate the toxic elements of PP. Similarly, PLA estrogenic activity was removed in both PLA/PBAT blends. This study demonstrates the benefits of bioassay guidance in the development of safer and sustainable packaging alternatives to petroleum-based plastics. Manipulating the types of additives and their formulations alongside toxicological testing may further improve safety aspects.